If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1y = 5 Solving 3x + 1y = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 3x + 1y + -1y = 5 + -1y Combine like terms: 1y + -1y = 0 3x + 0 = 5 + -1y 3x = 5 + -1y Divide each side by '3'. x = 1.666666667 + -0.3333333333y Simplifying x = 1.666666667 + -0.3333333333y
| 8=2(w-2) | | -6u+7= | | 5+d=8d-7 | | 3/5c=2c-7 | | 9-q=5 | | 24/48=50/x | | x+y=10000 | | 12k-11k+2=16 | | 12-8(4-s)+3(s+3)=27 | | 3-2(x-5)=13 | | x(3+2)+9=2x-12 | | 8w+2w-2=18 | | 5c+12-3c=28 | | x-sqrt(40-3x)=0 | | 4x+5(3x-3)=6 | | 2m-4=10+18 | | x(x-3)(x+12)=324 | | 3x+6y=-9 | | 7x+4y=53500 | | 2m-4=10+16 | | F(t)=0.25t^2-0.5t+3.5 | | 26=-7x+5(x+8) | | c+4=3/4 | | 6x-(5x+4)=5x-32 | | -3t-8+7t=35+9t-2 | | 40.5=49+1.7(55-60) | | 6=7x+69 | | 14y=32 | | 10lnx=e^4 | | 6st-7su+5sv= | | y=11x^2+x+40 | | 3y=-2x+11 |